The plastic of the future: Determinants for switching intention from synthetic to biodegradable plastics among the young consumers - Moshood, Taofeeq D.; Nawanir, Gusman; Fatimah, Mahmud; Mohd Hanafiah, Ahmad; Fazeeda, Mohamad; Airin, AbdulGhani (Emerald, 2023)
Purpose; This study aims to examine the young Malaysian consumers’ switching intention from synthetic to biodegradable plastics. This research shows the factors affecting young Malaysian consumers’ switching intention towards biodegradable plastic rather than traditional plastic (synthetic plastics). In this study, there are three factors to be considered whether they influence the young consumers in Malaysia to change their intention towards biodegradable plastic. The three factors are environmental concern, knowledge and the perceived value of biodegradable plastic. However, biodegradable plastic’s switching intention is also affected by biodegradable plastic’s attitude, where the three factors influence this attitude. Thus, all variables are considered in this research to investigate the reasons for switching intention from synthetic to biodegradable plastics among young Malaysian consumers. Design/methodology/approach; In line with the recent economic growth, especially in developing countries, human concern for the environment has increased over time. This paradigm shift has influenced Malaysians to pay more attention to the issues related to synthetic plastics, especially in Malaysia itself. To reduce the use of synthetic plastic in Malaysia, this research is conducted to identify the young consumer’s behaviour in Malaysia towards the use of biodegradable plastics. In this study, the theory of planned behaviour (TPB) is broadened into three additional factors that potentially enhance the young consumer’s attitude and increase switching intention towards biodegradable plastics: environmental concern, knowledge and perceived value. The data were collected using a structured questionnaire via an online survey method. The structural equation modelling with SmartPLS 3 was used to analyse the data from a total of 162 respondents. The study’s key findings confirmed that switching intention towards biodegradable plastics is significantly influenced by environmental concern, perceived value, and attitude. This study also provided empirical evidence that the attitude acts as a mediator for the relationship between environmental concern and perceived value towards the switching intention. These results could help the government establish a new policy to encourage citizens to use biodegradable plastics while reducing environmental pollution. Findings; The study’s key findings confirmed that switching intention towards biodegradable plastics is significantly influenced by environmental concern, perceived value and attitude. Furthermore, this study extends the TPB to include the intention to switch from synthetic to biodegradable plastics, where attitudes towards the environment, environmental concern and perceived value all have an impact on the intention to switch from synthetic to biodegradable plastics in the first place. As an additional contribution to the existing body of knowledge, this study provides empirical data about the variables influencing decision-makers’ intentions towards the transition from synthetic to biodegradable plastics. The findings of this study may also be useful for future research by academic institutions, the Department of Research and Development and the government. As a result, this research is important for future academics who want to better understand the intentions of young Malaysian consumers when it comes to biodegradable plastics. Originality/value; This research might provide direction to a firm considering implementing a new business strategy to develop creative and sustainable products that will contribute to the protection of the environment. More importantly, this research contributes to improving government policy and regulation in environmental preservation by integrating environmental knowledge and attitude into Malaysian cultural practices. Also possible are even greater levels of environmental awareness and environmentally friendly activities on the part of the government and the commercial sector, such as various initiatives and events to encourage green and environmentally friendly purchasing habits. As a result, given that sustainability has emerged as one of the most pressing issues facing society today, this research is important in that it provides insights for stakeholders (policymakers, marketers and others) to strategise the government’s plan to reduce the use of synthetic plastics and promote the use of biodegradable plastics. As the analysis of consumer behaviour is one of the most important aspects of improving the profitability of businesses, the collaboration between marketing and the research and development department to examine consumer behaviour is extremely important to meet the needs of consumers. This research could serve as a reference for them during the decision-making process, particularly in the plastics industry, which is highly recommended. Aside from that, the findings of the study may be used as a guide for the government in developing new policies to attain the objective of sustainable development in the future. As a result, it can aid in introducing environmentally friendly products and raising public knowledge about them.